Selecting Extensive Reading Materials - Jacobs, George M (Beyond Words, 2014)
This article offers guidance to teachers and students in selecting materials for extensive reading (ER). First, the article explains characteristics of ER and reviews some of the potential gains for students who do ER. Second, the article considers criteria for teachers to bear in mind when selecting ER materials. Third, the article then suggests ways that teachers and students can find ER materials. Fourth, guidance is provided to students for when they select what to read from among the ER materials available to them. Finally, advice is given on integrating ER with course textbooks.